The next SSM term: Supervisory challenges ahead - Martin Götz; Tobias Tröger; Mark Wahrenburg (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
In this note, we first highlight different developments for banks under direct ECB supervision within the SSM that may prompt further investigation by supervisors. We find that banks that were weakly capitalized at the start of direct ECB supervision (1) still face elevated levels of non-performing loans, (2) are less cost-efficient and (3) reduced their share of subordinated debt financing over the last years. We then stress the importance of continuous and ongoing cost-benefit analysis regarding banking supervision in Europe. We also encourage processes to question existing supervisory practices to ensure a lean and efficient banking supervision. Finally, we underline the need of continuous and intensified coordination among regulatory bodies in the Banking Union since the efficacy of European bank supervision rests on its interplay with many different institutions.
urn:nbn:de:hebis:30:3-489064
Keywords: 330; SSM; Banking Union; ECB supervision